DESAIN DAN SIMULASI SISTEM HMI (Human Machine Interface) BERBASIS CITECT SCADA PADA KONVEYOR PROSES DI INDUSTRI - Priswanto Priswanto; Tegar Herdantyo; Daru Tri Nugroho; Yogi Ramadhani; Agung Mubyarto (Universitas Muhammadiyah Semarang, 2018)
The conveyor system is a technology for transfer object to processing in industry from one place to another. The process in the industry such as quality control, packing product, assembly, etc. Conveyor technology is needed in the industrial process automation. The application of conveyor system technology in the industry requires acquisition data and control, so that each process on the industrial conveyor can be monitored and even controlled from the control room. The one of technology for acqusition data and controling process of industry by centrally from the control room is the technology of HMI (Human Machine Interface). The development of this HMI technology can be complement PLC- based conveyor system technology, making it more flexible and efficient by providing visualization and even control of industrial processes. In this research, Modeling of HMI using Citect SCADA has been conducted for Acquisition Data and Controlling Process of Conveyor Systems in Industry. The model of HMI designed and made using Vijeo Citect SCADA by adjusting the form of process conveyor models in the industry including input and output system. Based on the research that has been done, the results of HMI can work well, with a 100% success percentage. This shows that the addition of the HMI module to the system does not affect the performance of the conveyor system, but with the HMI feature it will be easier to control the process in the industry from the control room. Keywords: HMI, conveyor, PLC, Citect SCADA, industry.